PERBEDAAN PERFORMA PERUSAAHN KEUARGA DAN PERUSAHAAN BUKAN KELUARGA: STUDI PADA INDEX PEFINDO25 - Adiwidjojo, Enrico Pranata; Robiyanto, Robiyanto (2020)
Family firms are companies that are controlled by family members through ownership and management. This study aims to observe the existence of cash holding, gender diversity, and performance in family and non-family firms. Purposive sampling in this study resulted in 47 samples of companies listed on the PEFINDO25 Index. In the selection of these samples found 26 family firm and 21 non-family firm. Test results in this study prove that there is a significant difference in cash holding. Cash holding at the family firm is larger, but variables other than cash holding do not show a significant difference. The implications of this study are for investors, governments, and corporate power holders as a reference for decision making.